2020
DOI: 10.1016/j.asmart.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Bankart repair: A matched cohort comparison of the modified Mason Allen method and the simple stitch method

Abstract: Introduction Arthroscopic Bankart repair (ABR) has become a standard treatment for recurrent anterior shoulder dislocation in cases with minimal bone loss. Using the standard Bankart repair technique, the failure rate has been reported to be approximately between 4 and 35%. In addition to the original injury, multiple pathologies can occur after a dislocation including a Bankart lesion, capsular redundancy and bone defects. In cases with no significant bone loss, soft tissue plays a major role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, Santos et al [13] studied the biomechanics of simple suture and modi ed Mason-Allen suture in the Bankart lesions swine model, and found that the modi ed Mason-Allen suture provides increased labrum height, and meanwhile, the modi ed Mason-Allen suture had the same biomechanical strength advantage as simple suture. Siripipattanamongkol et al [14] retrospectively analyzed 80 patients with Bankart lesions, followed up for at least 2 years, and conducted a comparative study on the e cacy of modi ed Mason-Allen suture and simple suture in the treatment of shoulder glenolip lesions. The results showed that both the two methods of glenolip suture restored the stability and range of motion of shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Santos et al [13] studied the biomechanics of simple suture and modi ed Mason-Allen suture in the Bankart lesions swine model, and found that the modi ed Mason-Allen suture provides increased labrum height, and meanwhile, the modi ed Mason-Allen suture had the same biomechanical strength advantage as simple suture. Siripipattanamongkol et al [14] retrospectively analyzed 80 patients with Bankart lesions, followed up for at least 2 years, and conducted a comparative study on the e cacy of modi ed Mason-Allen suture and simple suture in the treatment of shoulder glenolip lesions. The results showed that both the two methods of glenolip suture restored the stability and range of motion of shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…Modi ed Mason-Allen suture was originally used for hand surgery tendon suture, but now it is mainly used for rotator cuff tear, labrum of shoulder joint, meniscus posterior root and achilles tendon repair. Its characteristics are mainly characterized by "straddle" locking, strong tissue holding force and pull force, small suture cutting force and relatively simple execution [13][14][15]. Now, no clinical studies have reported functional outcomes of modi ed Mason-Allen suture therapy for CAI in ABG.…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanical benefit of the modified Mason-Allen suture was identical to that of the simple suture. Siripipattanamongkol et al [23] compared the efficacy of modified Mason-Allen suture and simple suture in the treatment of shoulder glenoid lesions using a retrospective analysis of 80 patients with Bankart lesions who were followed for at least 2 years. The results indicated that both the two glenoid sutures techniques restored the shoulder joint stability and range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is currently mostly employed for rotator cuff tear, labrum of the shoulder joint, meniscus posterior root, and Achilles tendon repair. Its characteristics are mainly characterized by "straddle" locking, strong tissue holding force and pull force, small suture cutting force, and relatively simple execution [22][23][24]. Currently, no clinical studies have reported functional outcomes of modified Mason-Allen suture therapy for CAI in ABG.…”
Section: Introductionmentioning
confidence: 99%
“…Siripipattanamongkol et al. 16 in a retrospective cohort study compared a group of 50 patients who underwent modified Mason–Allen Stitch for arthroscopic Bankart repair with a group of 30 patients who underwent a simple stitch arthroscopic Bankart repair and found in both groups excellent patient satisfaction and shoulder stability restoration at a minimum 2-year follow-up. The modified Mason–Allen stitch was, however, associated with better functional outcomes at the final follow-up, with a significantly improved Walch–Duplay score (87.2 vs 82.0; P = .035) and Rowe score (respectively 86.8 vs 76.3; P = .001) and a nonsignificant trend for a lower failure rate with, respectively, 6% and 10% ( P = .511).…”
Section: Discussionmentioning
confidence: 99%